2009
DOI: 10.1002/jsfa.3837
|View full text |Cite
|
Sign up to set email alerts
|

Low oxygen treatment prior to cold storage decreases the incidence of bitter pit in ‘Golden Reinders’ apples

Abstract: Application of a LOT prior to cold storage may be a promising strategy to reduce the incidence of BP and preserve fruit quality, which should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
5
10
0
Order By: Relevance
“…The BPLS associated with the BG method were less pronounced for all sample groups and seasons. Other methods consisting of modifying the atmosphere and achieving low O 2 levels to reduce postharvest bitter pit have also been reported (Hewett, 1984;Hewett and Thompson, 1989;Khan et al, 2006;Val et al, 2009;Pesis et al, 2010). Pesis et al (2010) and Val et al (2009) reported that low O 2 and 20 C short-term pre-treatments prior to cold storage, could help to reduce bitter pit during cold storage.…”
Section: Development Of Bitter Pit-like Symptomsmentioning
confidence: 94%
See 1 more Smart Citation
“…The BPLS associated with the BG method were less pronounced for all sample groups and seasons. Other methods consisting of modifying the atmosphere and achieving low O 2 levels to reduce postharvest bitter pit have also been reported (Hewett, 1984;Hewett and Thompson, 1989;Khan et al, 2006;Val et al, 2009;Pesis et al, 2010). Pesis et al (2010) and Val et al (2009) reported that low O 2 and 20 C short-term pre-treatments prior to cold storage, could help to reduce bitter pit during cold storage.…”
Section: Development Of Bitter Pit-like Symptomsmentioning
confidence: 94%
“…In contrast, postharvest reductions in bitter pit have been reported in association with modified atmospheres and low O 2 levels (Khan et al, 2006;Torres and Alegre, 2012). Pesis et al (2010) and Val et al (2009) showed that pre-treatments prior to cold storage involving low O 2 and short-term storage at 20 C were able to reduce the incidence of apple scald and bitter pit during cold storage.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative to the 1-MCP treatment is low O 2 storage for 10 days at 20 °C, before long-term storage at low temperature (0-4 °C) (Pesis et al, 2010;Val et al, 2010).…”
Section: Storage Of Fruitsmentioning
confidence: 99%
“…For mineral element determination, fruits were carefully washed as previously described (Val et al, 2010), and a 1-cm transverse section of the fruit was cut at the equator, the skin was carefully separated from the cortex, and aliquots of each tissue were prepared for analysis. For tissue element determination, peels were finely cut (< 1 mm thick) and mixed.…”
Section: Mineral Element Analysismentioning
confidence: 99%